Descriptive analysis of extra-curricular program outcome attaintment: A case study of Universiti Malaysia Pahang - Siti Zanariah, Satari; Nor Alisa, Mohd Damanhuri; Rozieana, Khairuddin; Roslinazairimah, Zakaria (Akademi Sains Malaysia, 2019)
This study presents the descriptive analysis of students’ performance in extra-curricular activities at Universiti Malaysia Pahang (UMP). The data analysed are students from all bachelor degree programme at UMP of year 2015 to 2018. First, we propose an upgrade reporting mechanism for extra-curricular program at UMP using an Extra Curricular Cumulative Grade Point Average (XCGPA) formula calculated based on the student’s merit scores that has been achieved continuously throughout their study period. The merit score is accumulated based on the activity involvement, role and achievement level with different weightages and mapped between the intended core values and the targeted attributes. For each attribute, a maximum merit score needed per semester and for the whole year of study is set at a fixed value. Then, the percentage score for each attribute is calculated and classified according to six Student Personality Trait Classifications. The students’ profile is developed and the attainment for each attribute is presented by a spider web. The students’ profile report may assist students in understanding their unique behaviours, interest and abilities, as well as giving chances to recruiters and employers in hiring a more suitable candidate for their company. The descriptive analysis shows the capability of the new reporting mechanism in displaying the students’ personality traits.